Medication Adherence: Modifiers and Improvement Strategies - Pagès-Puigdemont, Neus; Valverde-Merino, M Isabel (Ars Pharmaceutica (Internet), 2018)
Objective: To describe what factors may influence medication adherence and what interventions have been developed to improve it. Methods: A search of the most relevant research articles published on the subject was performed in the National Library of Medicine database, Washington, DC (MEDLINE: PubMed). Results: Medication adherence is a complex behavior that has been linked to many aspects, such as socio-economic status, the healthcare team and the healthcare system, condition-related factors, therapy-related factors, and patient-related factors. Many interventions have been developed to improve therapeutic adherence, however, none of them have proved to date to be effective in all patients and permanently. Interventions to enhance adherence can be differentiated in technical interventions, behavioral interventions or educational interventions. Conclusions: Medication adherence is a dynamic behavior influenced by a great variety of factors. Consequently, improvement strategies should be individualized for each patient.